2017
DOI: 10.1038/cddis.2017.396
|View full text |Cite
|
Sign up to set email alerts
|

Amlexanox, a selective inhibitor of IKBKE, generates anti-tumoral effects by disrupting the Hippo pathway in human glioblastoma cell lines

Abstract: Glioblastoma multiforme (GBM) is the most prevalent form of malignant brain tumor. Amlexanox, a novel compound, has been shown to have anti-cancer potential. In this study, the anti-tumoral effects and the underlying mechanisms of amlexanox were investigated. Amlexanox significantly suppressed proliferation and invasion and induced apoptosis in glioblastoma cells. Furthermore, we found that amlexanox altered the protein expression of the Hippo pathway by downregulating IKBKE. Our data indicates that IKBKE dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 44 publications
5
43
0
Order By: Relevance
“…To evaluate the effect of the association with TMZ and amlexanox on cell viability, the CCK-8 assay was conducted. U87 MG and primary GBM cells were treated with different doses of TMZ, amlexanox, alone or both for 24, 48, and 72 h. As expected, the inhibition of proliferation in both cell types was gradually ampli ed with an increased concentration of either agent alone (Fig 1a), which was consistent with previous studies [21,4]. Moreover, the proliferation of cells treated with the combination, whether U87 MG or primary GBM cells, was e caciously attenuated (Fig 1a).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…To evaluate the effect of the association with TMZ and amlexanox on cell viability, the CCK-8 assay was conducted. U87 MG and primary GBM cells were treated with different doses of TMZ, amlexanox, alone or both for 24, 48, and 72 h. As expected, the inhibition of proliferation in both cell types was gradually ampli ed with an increased concentration of either agent alone (Fig 1a), which was consistent with previous studies [21,4]. Moreover, the proliferation of cells treated with the combination, whether U87 MG or primary GBM cells, was e caciously attenuated (Fig 1a).…”
Section: Resultssupporting
confidence: 90%
“…The effect of TMZ or amlexanox alone on the IKBKE and AKT signaling pathways was rst evaluated. After treatment with the designated dose of either agent for 48 h in U87 MG and primary GBM cells, results were showed as Fig 4. The western blot assay indicated that TMZ induced the activation of AKT and AMPK and decreased the phosphorylation of mTOR; the activation of IKBKE was decreased after amlexanox treatment, which was consistent with previous studies [14,21,23]. After treating U87 MG and primary GBM cells with both agents, the results showed that TMZ combined with amlexanox resulted in enhanced reduction of p-AKT and p-mTOR.…”
Section: Amlexanox Promoted Tmz-induced Apoptosis Of Gbm Cellssupporting
confidence: 89%
“…The research also revealed that IKKε could accelerate EMT of GBM cells . Another IKKε selective inhibitor, amlexanox was reported to generate antitumor effects by disrupting the Hippo pathway in human GBM cell lines . We guess that MCCK1 may inhibit IKKε to play anticancer role, but the regulatory mechanism of MCCK1 need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Given the significant inhibitory role of YAP in innate antiviral immunity, IKKε-mediated YAP degradation relieved the repression of YAP on the innate antiviral response (50). On the contrary, another group identified IKKε to be a negative regulator of the Hippo pathway via mediating degradation of LATS1/2, suggesting a complicated role of IKKε in Hippo pathway (58) (Figure 2). cGAS-induced innate immune response was demonstrated to activate Hippo-signaling by increasing the expression of MST1 (59).…”
Section: Hippo-yap and Ifn-i Signalingmentioning
confidence: 99%